Tailoring Broadband Large Chiral Response in All-Dielectric Twisted L-shape Metamaterial Platforms - Kilic, Ufuk; Schubert, Eva; Argyropoulos, Christos; Schubert, Mathias ; 0000-0001-6238-663X (15th International Conference on Metamaterials, Photonic Crystals and Plasmonics, META 2025, Malaga, Spain, 2025-07-22 - 2025-07-25, 2025)
This study presents the fabrication of all-dielectric silicon-based twisted L-shape metamaterials using a two-step electron-beam glancing angle deposition approach. Systematic chiroptical characterization and optimization are performed through Mueller matrix generalized spectroscopic ellipsometry and finite element modeling, demonstrating tunable, broadband chirality response with potential applications in chiral-chemistry, quantum optics, and nanophotonics.